2021
DOI: 10.1080/10503307.2021.1930243
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the temporal associations between avoidance behavior and cognitions during the course of cognitive behavioral therapy for clients with symptoms of social anxiety disorder

Abstract: Exploring the temporal associations between avoidance behavior and cognitions during the course of cognitive behavioral therapy for clients with symptoms of social anxiety disorder, Psychotherapy Research,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Our second post hoc analysis indicated that this was not due to the omission of the variable depression in the model. It is therefore likely that other mechanisms were involved, for example, operating through mediators like anxiety cognitions and avoidance behavior [38].…”
Section: Discussionmentioning
confidence: 99%
“…Our second post hoc analysis indicated that this was not due to the omission of the variable depression in the model. It is therefore likely that other mechanisms were involved, for example, operating through mediators like anxiety cognitions and avoidance behavior [38].…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting study evaluating mechanisms of change asked an age-old question among CBT clinical researchers: “Does changing cognitions change behavior, or does changing behavior change cognitions?” Using a sample of patients with SAD who received CBT, the study found that avoidance behavior predicted cognitions at subsequent timepoints but not vice versa 68 . This is a fascinating finding showing the direct pathway from behavior to cognition but not the opposite, which is the more traditional way that the cognitive model is presented to patients.…”
Section: Recent Advances In Improving the Treatment Of Sadmentioning
confidence: 96%
“…Another process scale is the 28-item Social Behavior Questionnaire (SBQ) which measures the presence of avoidance and safety behaviours common in social anxiety disorder, including strategies for impression management (Gray et al ., 2019). These behaviours are at the core of most cognitive behavioural conceptualizations of the maintenance of social anxiety disorder, and are believed to maintain or perhaps even exacerbate dysfunctional patterns in cognition and emotion (Lervik et al ., 2022; Wong and Rapee, 2016). In line with this view, avoidance behaviours including as measured using the SBQ have been found to mediate the effect of CBT on social anxiety disorder (Santoft et al ., 2019b; Thew et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%